571 Evaluating Need for Follow up Polysomnograms after Adenotonsillectomy in children. (3rd May 2021) - Rao, Harish
Abstract: Introduction: Most children with Obstructive sleep apnea (OSA) undergo repeat polysomnogram (PSG) following adenotonsillectomy (T & A). Repeat PSG is often performed regardless of presence of symptoms of sleep disordered breathing after T & A. PSG data performed before and after T & A performed at our institution over past 2 years were reviewed. Data was collected on patient characteristics such as age, sex, BMI, comorbidities and AHI on pre-T & A study. Data was then analyzed looking at patient characteristics that can help predict significant OSA (AHI >5) in post T & A study. Methods: Retrospective review of 50 consecutive PSGs before and after T & A performed at our institution over past 2 years was performed. Data was collected on age, sex, Obstructive AHI, BMI, O2 nadir and comorbidities to identify patient characteristics to predict significant OSA (AHI>5) in the post T & A study. Results: Age range of our cohort was 2–16 years. Average age and BMI of our cohort was 5.8 years (median 5 years) and 16.6 respectively. 8 patients had significant OSA (AHI>5) in the after T & A study. AHI (>20) and increased BMI z-score at baseline was highly predictive of significant OSA (AHI>5) in the after T & A study. Conclusion: Based on our data, follow up PSG is warranted if AHI is >20/hour on baseline diagnostic PSG. Similarly, high BMI z-score at baseline study is also highly predictive of significant OSA (AHI>5) in the post T & A study. Most children with associated comorbidities with mild (AHI 2–5 hour), moderate (AHI 5–10/hour) and lower end of severe OSA (AHI 10–20/hour) do not need repeat PSG after T & A unless symptoms of sleep disordered breathing are present. We are analyzing larger PSG database to identify other patient characteristics that may signal need for follow up PSG. As PSGs are expensive and time consuming, follow up PSGs should be performed only if clinical suspicion for residual OSA is high to optimize resource utilization. Support (if any):